2001
DOI: 10.1080/00343400125457
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration and Specialization Patterns in Spain

Abstract: The aim of this paper is to analyse how economic integration in Europe has affected industrial geographical concentration in Spain and to explain the driving forces behind industry location. First, we construct regional specialization and geographical concentration indices for 50 Spanish provinces (NUTS III) and 30 industrial sectors in 1979, 1986 and 1992. Second, we carry out an econometric analysis of the determinants of the geographical concentration of industries. Our main conclusion is that there is no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
4
19
0
5
Order By: Relevance
“…These findings complement previous results and provide a new perspective on the evolution of the location pattern of industry in the Spanish regions from the mid19th century through the end of the 20th century Pons, 2002 andTirado, 2001). During that period, the geographic concentration of industrial activity, as noted previously, would seem to have followed an inverted-U shape characterised by an initial phase of growing concentration of industrial production which continued until the 1970s.…”
Section: Empirical Analysissupporting
confidence: 75%
“…These findings complement previous results and provide a new perspective on the evolution of the location pattern of industry in the Spanish regions from the mid19th century through the end of the 20th century Pons, 2002 andTirado, 2001). During that period, the geographic concentration of industrial activity, as noted previously, would seem to have followed an inverted-U shape characterised by an initial phase of growing concentration of industrial production which continued until the 1970s.…”
Section: Empirical Analysissupporting
confidence: 75%
“…The level of spatial concentration of sectoral production across EU countries is investigated by Amiti (1999) and Haaland et al (1999), the one across Spanish regions by Paluzie, Pons and Tirado (2001). These studies have identified a higher level of demand concentration, human capital, stronger scale intensity and intermediate-input intensity of a sector to increase its level of concentration while a high labour intensity seems to de-crease the sector's uneven allocation across space.…”
Section: Non-technical Summarymentioning
confidence: 99%
“…The level of sectoral concentration across EU countries is investigated by Amiti (1999) and Haaland et al (1999), the one across Spanish regions by Paluzie, Pons and Tirado (2001). These studies have identified a higher level of demand concentration, human capital, stronger scale intensity and intermediate-input intensity of a sector to increase its level of concentration while a high labour intensity seems to decrease the sector's uneven allocation across space 2 .…”
Section: Motivationmentioning
confidence: 99%